Successful administration of low-dose almonertinib in a patient with lung adenocarcinoma after osimertinib-induced interstitial lung disease: a case report and literature review. Issue 3 (14th November 2022) - Chen, Wenyan; Zhang, Lijuan; Shen, Hui; Wang, Bin; Luo, Jiayou; Cui, Enhai
Abstract : Osimertinib, the third generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), is the standard treatment for nonsmall cell lung cancer with EGFR mutation. However, osimertinib-induced interstitial lung disease (OsiILD) is considered to be a serious adverse event, so some patients will have to discontinue the use of osimertinib due to OsiILD. Almonertinib is a novel third-generation EGFR-TKI. We herein report a patient who developed OsiILD after the use of osimertinib and then switched to almonertinib for further treatment with success. This is the first report of a successfull rechallenge with low-dose almonertinib after OsiILD. We also reviewed the literature to explore the possible risk factors and the subsequent treatment of OsiILD, suggesting that low-dose almonertinib may be an option for follow-up treatment of OsiILD.